Seaberg Hotel
Later known as the El Portal
Black and White photographs
Master list item #: 4
File location is in the Raton file Cabinet
Keywords: Seaberg Hotel; Raton Hotel Photographs; Hotel Photographs; Building Photographs; Post Card Photographs; Raton, New Mexico